Analisis Beban Kerja Untuk Menentukan Jumlah Tenaga Kerja Yang Optimal - Prananta, Ilham Leo; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The development of production needs at CV. Berdikari requires the company to have optimal work capacity to meet market demand. However, actual conditions show a high workload and overtime hours in the production department. This study aims to analyze the level of work activity, measure the workload, determine optimal labor requirements, and evaluate alternatives for fulfilling work capacity. The Work Sampling method was used to randomly observe worker activities to obtain the proportion of productive, indirect, and non-productive time. The results showed that productive activity was in the high category, reflecting good work efficiency. However, the total overtime hours from January to June 2025 reached 2,339 hours, indicating that regular labor capacity was inadequate. Based on standard time calculations, the optimal labor requirement is 3–4 people.